A story from the Miocene: Clock‐dated phylogeny of Sisymbrium L. (Sisymbrieae, Brassicaceae). Issue 6 (2nd March 2021) - Žerdoner Čalasan, Anže; German, Dmitry A.; Hurka, Herbert; Neuffer, Barbara
Abstract: Morphological variability and imprecise generic boundaries have hindered systematic, taxonomical, and nomenclatural studies of Sisymbrium L. (Brassicaceae, Sisymbrieae DC.). The members of this almost exclusively Old‐World genus grow mostly on highly porous substrates across open steppe, semidesert, or ruderal habitats in the temperate zone of the Northern Hemisphere and African subtropics. The present study placed the biological history of Sisymbrium L. into time and space and rendered the tribus Sisymbrieae as monotypic. Five nuclear‐encoded and three chloroplast‐encoded loci of approximately 85% of all currently accepted species were investigated. Several accessions per species covering their whole distribution range allowed for a more representative assessment of intraspecific genetic diversity. In the light of fossil absence, the impact of different secondary calibration methods and taxon sets on time spans was tested, and we showed that such a combinatorial nested dating approach is beneficial. Multigene phylogeny accompanied with a time divergence estimation analysis placed the onset and development of this tribus into the western Irano‐Turanian floristic region during the Miocene. Continuous increase in continentality and decrease in temperatures promoted the diversity of the Sisymbrieae, which invaded the open grasslands habitats in Eurasia, Mediterranean, and South Africa throughout the Pliocene and Pleistocene. Our results support the assumption of the Irano‐Turanian region as a biodiversity reservoir for adjacent regions. Abstract : Morphological variability and imprecise generic boundaries have hindered systematic, taxonomical, and nomenclatural studies of Sisymbrium L. (Brassicaceae, Sisymbrieae DC.). The present study placed the biological history of Sisymbrium L. into time and space and rendered the tribus Sisymbrieae as monotypic. It appears that palaeogeographical and palaeoenvironmental events during the Pliocene and Pleistocene are the main driving forces behind the evolutionary history of many Sisymbrieae species.